Factors Affecting the Behavior of Family Planning Field Officers in the Achievement of New Family Planning (KB) Participants in Karawang - Intan Ratna Wati; Nanik Yuliwati (Asian Journal of Community Services, 2023)
The family planning service program from the BKKBN is inseparable from PLKB/PKB (Family Planning Field Extension/Family Planning Extension) which is the spearhead as an interpreter or agent of change for families and the wider community. The purpose of this study was to determine the factors that influence the behavior of family planning field workers (PLKB) in achieving new family planning participants in Karawang Regency in 2022. This study used an analytic method with a cross sectional research design.The population in the study were all Family Planning Field Officerswhich totaled 163 people. Samples taken based on statistical tests amounted to 62 people. The sampling technique used in this research is purposive sampling. Data analysis was performed, namely education with a value of P=0.032 and OR=0.50, KIE with a value of P=0.018 and OR=2.60, and motivation with a value of P=0 , 046 and OR=1.66. Of the 3 independent variables, it has been tested statistically that the effect of PLKB behavior on achieving new KB is influenced by education, KIE and PLKB motivatio.